Wood adhesives from waste-free recycling depolymerisation of flexible polyurethane foams. (10th July 2021) - Beran, Rudolf; Zárybnická, Lucie; Machová, Dita; Večeřa, Miroslav; Kalenda, Petr
Abstract: Flexible polyurethane foams (FPUF) are common plastic materials used in industry or consumer goods (heat and sound insulation, washing sponges, car seats). FPUF wastes are frequently taken to landfills and incineration, which causes environmental problems. The current method of physical recycling for rebound foams seems to be efficient, however, with limited usage in the structure of mattresses or construction insulations. Disadvantages of the current chemical recycling methods of FPUF consist of the slow reaction process, high energy consumption, and production of secondary waste by-products. This article deals with the special technique of the controlled depolymerisation of the studied FPUF. FPUF was depolymerised in an ambience of non-reactive liquid at a temperature of 130 °C, only giving liquid products. The depolymerisation process and the final product was characterised by titration methods, Fourier Transform-Infrared Spectroscopy (FT-IR), Gas Chromatography/Mass Spectrometry (GC/MS), and Gel Permeable Chromatography (GPC). The recycled polyol (product of depolymerisation) was tested in model polyurethane adhesive formulations and evaluated for shear tensile strength on spruce wood test pieces. Graphical abstract: Image 1 Highlights: Wastes from flexible polyurethane foam are taken to landfills and incinerated, causing environmental problems. The traditional recycling approach was related to the generation of by-products requiring a significant energy input. The new recycling approach is energy favorable and all products recovered can be processed and re-used. The research proposes the use of recovered polyol in adhesive formulations for wood specimens.